1987
DOI: 10.1111/j.1471-0528.1987.tb03152.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with oral piperazine oestrone sulphate for genuine stress incontinence in postmenopausal women

Abstract: Summary The use of oestrogens in the treatment of genuine stress incontinence was assessed by a double‐blind prospective trial in 36 postmenopausal women with genuine stress incontinence who received 3 months of cyclical treatment with either piperazine oestrone sulphate or a matching placebo. Patients were assessed subjectively and objectively before and after treatment by 7‐day bladder charts, urethral pressure profiles (UPP), the Urilos nappy test, vaginal cytology and hormone assays (plasma oestrogens and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(23 citation statements)
references
References 18 publications
0
21
0
2
Order By: Relevance
“…2,11 In clinical practice, however, the reported e ects of estrogen treatment, in terms of cure rates and urethral pro®le measurements, are con¯icting. 3,4,12,13 These aspects con®rm, as is known, that UPP is of limited practical value in studying continence or in the follow-up of incontinent patients undergoing estrogen therapy.…”
Section: Discussionmentioning
confidence: 99%
“…2,11 In clinical practice, however, the reported e ects of estrogen treatment, in terms of cure rates and urethral pro®le measurements, are con¯icting. 3,4,12,13 These aspects con®rm, as is known, that UPP is of limited practical value in studying continence or in the follow-up of incontinent patients undergoing estrogen therapy.…”
Section: Discussionmentioning
confidence: 99%
“…70 Although a few studies employing objective measures of stress urinary incontinence have yielded disappointing results, 70,71 subjective improvement with estrogen therapy has been reported, and several studies have demonstrated symptomatic relief of urinary complaints following HRT. For example, Raz et al 72 reported that a majority of their subjects had increased maximum urethral pressures with CEE (2.5 mg/day), and Walter et al 73 reported decreased objective measures of urine loss with estriol therapy.…”
Section: Urinary Functionmentioning
confidence: 97%
“…11,12 Üriner inkontinans, yaşlanma ile birlikte sıklığı artan önemli geriatrik sendromlardan biridir. Toplumda yaşayan 60 yaş ve üzerindeki hastalarda prevalans %8-18 arasında iken, kadınlarda erkeklere nazaran 2 kat daha fazla görülmektedir.…”
Section: Gereç Ve Yöntemlerunclassified